2017
DOI: 10.1200/jco.2017.35.15_suppl.6615
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a financial toxicity (FT) grading system.

Abstract: 6615 Background: FT is an important adverse event (AE) that should be objectively measured in clinical practice. We previously developed an evidence-based FT grading system based on differences in HRQoL, analogous to the NCI-Common Terminology Criteria for Adverse Events (grade 1, mild AE; grade 2, moderate AE; grade 3, severe AE ,de Souza et al - ASCO 2015). We aimed to validate this grading system using a new sample of cancer patients (pts) and report its association with bankruptcy. Methods: FT was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…5 6 Various thresholds for financial toxicity have been proposed using the COST score, often based on the median or percentile within discrete patient cohorts. [7][8][9] A system proposed by the creators of the COST tool used effect sizes for quality of life scores to develop financial toxicity grades (grades 0-3) using COST scores. The grading system was further validated based on the odds of patients declaring bankruptcy within each group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 6 Various thresholds for financial toxicity have been proposed using the COST score, often based on the median or percentile within discrete patient cohorts. [7][8][9] A system proposed by the creators of the COST tool used effect sizes for quality of life scores to develop financial toxicity grades (grades 0-3) using COST scores. The grading system was further validated based on the odds of patients declaring bankruptcy within each group.…”
Section: Introductionmentioning
confidence: 99%
“…The grading system was further validated based on the odds of patients declaring bankruptcy within each group. 9 Currently, there are limited data on what levels of financial toxicity measured by COST are linked to costcoping strategies such as economic behavior change and non-compliance with medications, which can lead to clinically meaningful worse health outcomes. 7 8 There have been two single institution studies examining financial toxicity using the COST tool in patients with gynecologic cancer, which found that 40-50% of patients experience financial toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the toxicities associated with cancer therapies, the financial toxicity associated with cancer care is becoming increasingly relevant in the face of rising cancer care costs and given that out-of-pocket expenses, copayments, and insurance premiums can often cause significant financial stress and burden to cancer patients that can adversely affect QOL and outcomes [ 21 , 22 ]. Accordingly, evidence-based financial toxicity grading systems analogous to the NCI-Common Terminology Criteria for Adverse Events grading system have been developed and are undergoing validation [ 215 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer has been identified as a fatal disease, a growing health concern and economic burden worldwide (1)(2)(3). During the past decade, with the help of medical advancements in early detection, the survival rate of cancer patients has risen with a concomitant increase in treatment costs (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Japanese version (12) and Chinese version (16) of the COST have shown good reliability and validity. However, in less developed societies that are expected to face more difficulties (mortality and costs) among cancer patients and their family, research is relatively scarce (1)(2)(3)17). Besides income, patients from different social, and cultural backgrounds may experience different financial toxicity.…”
Section: Introductionmentioning
confidence: 99%